Youth Culture and Cell Phone - mohammad saeed zokaei; Vahid Valizadeh (Taḥqīqāt-i Farhangī-i Īrān, 2009)
Iranian youth’s leisure culture has been immediately affected by the digital media culture. As a communicative media, cell phone has crossed borders of youth norms and identity; and in addition to facilitating their communication, has changed its patterns. Applying Bourdieu’s concepts of habitus and field, and relied on the qualitative and quantitative data gathered from the mobile youth users, the present study argues that mobile has produced a new field in which youth’s opportunities for leisure, entertainment, communication, and independence have extended. In addition, cell phone has facilitated and compensated for some defects in public sphere, and therefore empowered youth agency, individuality, and power. Despite this strengthening, cell phone does not cross borders of gender and class differences, or the levels of social capital.